Methicillin and Vancomycin Resistant S. aureus in Hospitalized Patients - Loomba, Poonam Sood (Medknow Publications, 2010)
S. aureus is the major bacterial cause of skin, soft tissue and bone infections, and one of the commonest causes of healthcare-associated bacteremia. Hospital-associated methicillin-resistant S. aureus (MRSA) carriage is associated with an increased risk of infection, morbidity and mortality. Screening of high-risk patients at the time of hospital admission and decolonization has proved to be an important factor in an effort to reduce nosocomial transmission. The electronic database Pub Med was searched for all the articles on “Establishment of MRSA and the emergence of vancomycin-resistant S. aureus (VRSA).” The search included case reports, case series and reviews. All the articles were cross-referenced to search for any more available articles. A total of 88 references were obtained. The studies showed a steady increase in the number of vancomycin-intermediate and vancomycin-resistant S. aureus. Extensive use of vancomycin creates a selective pressure that favors the outgrowth of rare, vancomycin-resistant clones leading to heterogenous vancomycin intermediate S. aureus hVISA clones, and eventually, with continued exposure, to a uniform population of vancomycin-intermediate S. aureus (VISA) clones. However, the criteria for identifying hVISA strains have not been standardized, complicating any determination of their clinical significance and role in treatment failures. The spread of MRSA from the hospital to the community, coupled with the emergence of VISA and VRSA, has become major concern among healthcare providers. Infection-control measures, reliable laboratory screening for resistance, appropriate antibiotic prescribing practices and avoidance of blanket treatment can prevent long-term emergence of resistance.